Hypoglycemic activity and stability enhancement of human insulin–tat mixture loaded in elastic anionic niosomes - Aranya Manosroi (2018)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. This study aimed to investigate the synergistic effect of trans-activator of transcription (Tat) and niosomes for the improvement of hypoglycemic activity of orally delivered human insulin. The elastic anionic niosomes composing of Tween 61/cholesterol/dicetyl phosphate/sodium cholate at 1:1:0.05:0.02 molar ratio loaded with insulin–Tat mixture (1:3 molar ratio) was prepared. Deformability of the elastic anionic niosomes decreased after loaded with the mixture of 1.35 times. For the in vitro release, the insulin (T10 = 4 h) loaded in the elastic anionic niosomes indicated the slower release rate than insulin in the mixture (T10 = 3 h) loaded in niosomes. At room temperature (30 ± 2 °C), the mixture loaded in elastic anionic niosomes was more chemical stable than the free mixture of 1.3, 1.4 and 1.7 times after stored for 4, 8 and 12 weeks, respectively. Oral administration in the alloxan-induced diabetic mice of the mixture loaded in elastic anionic niosomes with the insulin doses at 25, 50 and 100 IU/kg body weight indicated significant hypoglycemic activity with the percentage fasting blood glucose reduction of 1.95, 2.10 and 2.10 folds of the subcutaneous insulin injection at 12 h, respectively. This study has demonstrated the synergistic benefits of Tat and elastic anionic niosomes for improving the hypoglycemic activity of the orally delivered human insulin as well as the stability enhancement of human insulin when stored at high temperature. The results from this study can be further developed as an effective oral insulin delivery.